Effects of cold-pressed wheat germ oil and Bacillus subtilis on growth performance, digestibility, immune status, intestinal microbial enumeration, and gene expression of broilers under heat stress - Abdel-Moneim Eid Abdel-Moneim; Safaa A.M. Ali; M.G. Sallam; Ahmed M. Elbaz; Noura M. Mesalam; Zangabel S. Mohamed; AbdelRahman Y Abdelhady; Bing Yang; Mohamed Farouk Elsadek (Poultry Science)
This study evaluated the effect of wheat germ oil (WGO), Bacillus subtilis, and their combination on growth performance, immune response, nutrient digestibility, intestinal microbial, oxidative status, and gene expression in heat-stressed broilers. Four hundred one-day-old male Ross 308 broilers were distributed into five pens (20 birds/pen) in four experimental groups: a control (CON) without additives, WGO group fed diet with WGO at 200 mg.kg-1, BS group fed diet with B. subtilis at 500 mg.kg-1 containing 5 × 108 CFU.g-1, and CWB group received both WGO and B. subtilis. Heat stress exposure adversely affected broiler growth performance, carcass traits, immune response, and insulin-like growth factor 1 (IGF-1) and mucin2 (MUC2) mRNA expression. However, the CWB group showed a lower FCR, reduced mortality rate, and increased BWG compared to the other groups. Nutrient digestion was also improved, with a higher digestibility of ether extract, dry matter, and crude protein. By day 35, stress biomarkers like corticosterone and glucose levels were reduced, while triiodothyronine levels increased in the BS and CWB groups. The CWB group also showed lower malondialdehyde and interleukin-6 levels, with higher superoxide dismutase activity, and increased levels of IgA, IgG, and interleukin-10. Additionally, the CWB group had higher HDL levels and lower cholesterol and LDL levels (P < 0.05). Notably, CWB supplements modified the structure of the cecal microbial community by increasing Lactobacillus counts and decreasing E. coli and C. perfringens counts. Furthermore, the expressions of intestinal MUC2 and hepatic IGF-1 were up-regulated (P < 0.05) in the CWB group. This study provides evidence that supplementing heat-stressed broiler diets with a mixture of WGO and B. subtilis enhances antioxidant capacity, immune response, growth performance, and gut integrity via modulating the microbial community and regulating gene expression.